2007
DOI: 10.1016/j.chembiol.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Gold(III)-Dithiocarbamato Complexes Induce Cancer Cell Death Triggered by Thioredoxin Redox System Inhibition and Activation of ERK Pathway

Abstract: Although gold compounds are now recognized as promising anticancer agents, so far only gold(I) derivatives have been investigated for this purpose, whereas the use of gold(III) complexes has been hampered by their poor stability under physiological conditions. We have therefore carried out studies on selected gold(III) anticancer agents, showing enhanced stability due to the presence of chelating dithiocarbamato ligands. We found that they induce cancer cell death through both apoptotic and nonapoptotic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 52 publications
8
107
0
1
Order By: Relevance
“…In this regard, proteasome has been recognized as a major in vitro and in vivo target, 14,15 as well as the selenoenzyme thioredoxin reductase, both cytosolic and mitochondrial. 16,17 The choice of the ligands was not accidental. As previously reminded, nephrotoxicity (i.e., renal toxicity) is a major drawback in platinum-based chemotherapy.…”
mentioning
confidence: 99%
“…In this regard, proteasome has been recognized as a major in vitro and in vivo target, 14,15 as well as the selenoenzyme thioredoxin reductase, both cytosolic and mitochondrial. 16,17 The choice of the ligands was not accidental. As previously reminded, nephrotoxicity (i.e., renal toxicity) is a major drawback in platinum-based chemotherapy.…”
mentioning
confidence: 99%
“…The antiproliferative activities of gold-2a in MDA-MB-231 cells were comparable with other HDACi, such as SAHA (43) and TSA (44). Previous studies have suggested that cisplatin and gold (III) porphyrin complexes elicit their anticancer effects through distinct mechanisms at the DNA level and the protein level, respectively (45)(46)(47)(48). Among the five types of human breast cancer cells, MDA-MB-231 possesses the most active autocrine canonical Wnt signaling, followed by SKBR3, T47D, MCF-7, and BT474 (16,49), indicating that gold-2a may favor on targeting cancers that are more addicted to Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…As a result gold(III) compounds have been thought to have therapeutic effects similar to cisplatin. Research on gold(III) compounds as potential anticancer agents has been reported (Saqqioro et al 2007;Keter et al 2008;Angela et al 2008). There are a few examples of gold(III) compounds that have been reported to show activity against HIV.…”
Section: Gold(iii) Compoundsmentioning
confidence: 99%